Malaria, sex, and place of residence as factors in antibody response to Epstein-Barr virus in Ghana, West Africa. - Biggar, R.J.; Gardiner, C.; Lennette, E.T.; Collins, W.E.; Nkrumah, F.K.; Henle, W. (Lancet, 1981)
Both Epstein-Barr virus and malaria have been implicated as possible factors in Burkitt's lymphoma. To examine this implication a cross-sectional serological survey of an urban and a rural population in Ghana was conducted. Malaria was more prevalent in the rural areas, but there was no difference in antiviral capsid antigen (VCA) antibody titres between urban and rural dwellers. There was also no correlation between anti-malaria antibody titres and anti-VCA antibody titres. Thus malaria does not seem to influence immunological response to Epstein-Barr virus infection, as measured by anti-VCA antibodies. These results suggest that if Epstein-Barr virus infection and malaria are important in the aetiology of Burkitt's lymphoma, they produce their effects independently. The survey also showed that those in rural areas seroconverted earlier than those in urban areas, and that antibody levels were consistently higher in females than in males in every age-group. Case-control studies and screening programmes involving anti-VCA levels will therefore have to take these two findings into account.